Rapid and Sensitive Immunochromatographic Strip for On‐site Detection of Sulfamethazine in Meats and Eggs. Issue 10 (11th September 2013) - Shim, Won‐Bo; Kim, Jeong‐Sook; Kim, Min‐Gon; Chung, Duck‐Hwa
Abstract A rapid immunochromatographic (ICG) strip based on a conjugate of colloidal gold and monoclonal antibody (mAb) was developed for the rapid, sensitive, and on‐site detection of sulfamethazine in meat and egg samples. The detection limit of the ICG strip is 2 ng/mL, and the assay can be completed in 10 min. A cross‐reactivity test indicated that the ICG strip was highly specific to sulfamethazine with no cross‐reaction with sulfonamide compounds and other antibiotics. The results of the recovery test from meat and egg samples spiked with sulfamethazine were in good agreement with those obtained by the indirect competitive enzyme‐linked immunosorbent assay. These results demonstrated that the ICG strip can be used as a rapid and qualitative tool for on‐site screening of sulfamethazine in meat and egg samples.